Effects of Tween 80 on Growth and Biofilm Formation in Laboratory Media - Nielsen, Christina K.; Kjems, Jørgen; Mygind, Tina; Snabe, Torben; Meyer, Rikke L. (Frontiers in Microbiology, 2016)
Tween 80 is a widely used non-ionic emulsifier that is added to cosmetics, pharmaceuticals, and foods. Because of its widespread use we need to understand how it affects bacteria on our skin, in our gut, and in food products. The aim of this study is to investigate how Tween 80 affects the growth and antimicrobial susceptibility of Staphylococcus aureus, Listeria monocytogenes, and Pseudomonas fluorescens, which are common causes of spoilage and foodborne illnesses. Addition of 0.1% Tween 80 to laboratory growth media increased the growth rate of planktonic S. aureus batch cultures, and it also increased the total biomass when S. aureus was grown as biofilms. In contrast, Tween 80 had no effect on batch cultures of L. monocytogenes, it slowed the growth rate of P. fluorescens, and it led to formation of less biofilm by both L. monocytogenes and P. fluorescens. Furthermore, Tween 80 lowered the antibacterial efficacy of two hydrophobic antimicrobials: rifampicin and the essential oil isoeugenol. Our findings underline the importance of documenting indirect effects of emulsifiers when studying the efficacy of hydrophobic antimicrobials that are dispersed in solution by emulsification, or when antimicrobials are applied in food matrixes that include emulsifiers. Furthermore, the species-specific effects on microbial growth suggests that Tween 80 in cosmetics and food products could affect the composition of skin and gut microbiota, and the effect of emulsifiers on the human microbiome should therefore be explored to uncover potential health effects.